Pembuatan Dan Karakterisasi Serta Penentuan Kadar Flavonoid Dari Ekstrak Kering Herba Meniran (Phyllanthus niruri L.) - Krisyanella Krisyanella; Nana Susilawati; Harrizul Rivai (Jurnal Farmasi Higea, 2013)
Preparation and characterization of dried herb extract of meniran (Phyllanthus niruri L.) has been done. Dried extract was made by adding lactose with a certain ratio, with the ratio of extract and lactose are: 1 : ½ (F1); 1 : 1 (F2); 1 : 1½ (F3); 1 : 2 (F4). Characters abserved were specific and non specific character of  the dried extract. Non specific character of dry extract include loss in drying values, real density, compressed  density, total ash, acid insoluble ash content. Specifik characterization extract includes identities, organoleptic, levels of water soluble exstract the levels of compounds soluble in ethanol and levels of chemical constituents. Dried extract mode with F3 has better characteristics than the other formulas. The name of the extract is Extractum Phyllanthus niruri L.Siccum. The extract was in the form of dry powder, dark brown, odor like meniran crude herb with a strong flavor. Levels of water soluble extract was 55.1077 % b/b ± 11.2218 % b/b while levels of ethanol-soluble extract 18.7214 % b/b ± 0.6733 % b/b. flavonoid levels of the dried extract was 0.2413 % w/w.